Mapping Topic Relationships in Metaverse Research in Digital Business : A Co-Occurrence Approach - Suryopratomo, Anggit (Masoem University, 2025)
The metaverse, a virtual world integrated with real life, has attracted significant attention from both academic and industrial research communities. Projections estimate a market value of 800 billion by 2024. However, the majority of metaverse research to date has focused exclusively on technical aspects and specific applications. This research aims to map the inter-topic relationships in metaverse literature and digital business through bibliometric analysis, specifically co-occurrence analysis, to identify existing trends and patterns. Quantitative analysis, through bibliometric evaluation and descriptive statistics, was performed on the Scopus database, yielding 130 relevant articles from 2000 to 2024. The results indicated that